2020
DOI: 10.1016/j.esxm.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pulmonary Oil Microembolism After Testosterone Undecanoate Injection: A Postmarketing Safety Analysis

Abstract: Background: The Aveed Risk Evaluation and Mitigation Strategy program was instituted because of potential risk of pulmonary oil microembolism (POME) and/or anaphylaxis after intramuscular injection of Aveed (testosterone undecanoate), indicated for treatment of adult male patients with congenital or acquired primary hypogonadism or hypogonadotropic hypogonadism. Aim: To analyze the reporting rate of POME associated with testosterone undecanoate administration (750 mg/ 3 mL) during postmarketing surveillance. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is clinically characterized by acute onset (<1 hour) of cough, likely resulting from the inadvertent injection of the oil formulation into the venous system. 30 Topical testosterone therapy (gel/patch), although less invasive and easier to administer, can have variable absorption, risk of contact spread to females/children in the immediate family and contact allergies. Intranasal applications must be done thrice daily, which can be cumbersome and have nasal side effects.…”
Section: Challenges Of the Existing Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clinically characterized by acute onset (<1 hour) of cough, likely resulting from the inadvertent injection of the oil formulation into the venous system. 30 Topical testosterone therapy (gel/patch), although less invasive and easier to administer, can have variable absorption, risk of contact spread to females/children in the immediate family and contact allergies. Intranasal applications must be done thrice daily, which can be cumbersome and have nasal side effects.…”
Section: Challenges Of the Existing Formulationsmentioning
confidence: 99%
“…It is clinically characterized by acute onset (<1 hour) of cough, likely resulting from the inadvertent injection of the oil formulation into the venous system. 30 …”
Section: Challenges Of the Existing Formulationsmentioning
confidence: 99%
“…A recent postmarketing safety analysis demonstrated that pulmonary oil microembolism events related to IM TU therapy were rare and resolved quickly without medical intervention in the majority of cases reported. The most severe cases were associated with nonlabeled adherent injection techniques or dosing errors [79].…”
Section: Long-acting Im Formulationmentioning
confidence: 99%
“…IM-injected TU has the longest duration of action [ 88 ]. However, its use is restricted because of rare associated cases of pulmonary oil microembolism [ 89 ]. Furthermore, its use in pediatrics is limited because of dosing and its long washout period, should complications arise.…”
Section: Current Options For Testosterone Therapy In Adolescents Amentioning
confidence: 99%